Inflation trends in Asia: Implications for central banks - Juan Angel Garcia; Aubrey Poon (European Central Bank (ECB), 2019)
Trend inflation estimates for 12 of the largest Asian economies over 1995-2018 offer important insights on inflation dynamics and inflation expectations. The disinflationary shocks that hit the region since 2014 were partly transitory, but their effects have been different depending on the behaviour of trend inflation in each country. Countries with relatively high inflation (India, Philippines, Indonesia) benefited, and some were impacted very mildly (China, Taiwan, Hong Kong SAR, Malaysia). Among countries with inflation below target, in those with trend inflation low but constant (Australia, New Zealand) low inflation maybe lasting, but temporary, while those in which trend inflation has declined (South Korea, Thailand) risk low inflation to become entrenched and a de-anchoring of expectations. This diverse international evidence could offer important lessons for monetary policy worldwide.
Keywords: C11; C32; E31; F41; 330; trend inflation; survey inflation expectations; Asian economies; state space model; stochastic volatility